2015
DOI: 10.1103/physrevb.92.094434
|View full text |Cite
|
Sign up to set email alerts
|

Dzyaloshinskii-Moriya interaction mediated by spin-polarized band with Rashba spin-orbit coupling

Abstract: Dzyaloshinskii-Moriya interaction (DMI) plays a central role in breaking chiral symmetry of magnetic domain wall structure. The recently observed chiral dependence of domain wall structures in ultrathin magnetic films with perpendicular anisotropy indicates the presence of a strong DMI.We calculate the indirect exchange interaction between magnetic ions mediated by spin-polarized conduction electrons with a Rashba spin-orbit coupling. We find the resulting DMI increases with the spin-orbit coupling strength, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(40 citation statements)
references
References 24 publications
2
38
0
Order By: Relevance
“…According to the latter 38,39,40 , the DMI parameter can be roughly expressed as = 2 R , where A is the exchange stiffness and R = 2 R ℏ 2 is determined by the Rashba coefficient, R , and effective electron mass, me. The latter in Co was measured to be about 0.45 m0 41 (with m0 being the rest mass of electron), and the exchange stiffness, A, was found to be about 15.5 ×10 -12 J/m 32,42 .…”
Section: First-principles Calculationsmentioning
confidence: 99%
“…According to the latter 38,39,40 , the DMI parameter can be roughly expressed as = 2 R , where A is the exchange stiffness and R = 2 R ℏ 2 is determined by the Rashba coefficient, R , and effective electron mass, me. The latter in Co was measured to be about 0.45 m0 41 (with m0 being the rest mass of electron), and the exchange stiffness, A, was found to be about 15.5 ×10 -12 J/m 32,42 .…”
Section: First-principles Calculationsmentioning
confidence: 99%
“…It is then possible to take advantage of this spin current with the only difference that now both charge and spin currents are orthogonal to each other in a typical multilayer system. Charge current is flowing along the interface while spin current is diffusing perpendicularly to the interface of the constitutive layers.In this vein, several experiments have been designed to demonstrate the possibility of reversing the magnetization in single ferromagnetic layer or to propagate domain walls (DWs) using materials with strong SHE [3][4][5][6][7][8].Unfortunately the exact origin of the process as well as its microscopic understanding were still far from being fully understood at the present stage [9][10][11][12][13]. Since the pioneering work from Miron et al, [3] several reports have shown some possible routes or scenarios to explain either magnetization reversal [4,[14][15][16][17][18][19][20][21] or DW propagation [5][6][7][8][22][23][24][25][26][27][28].…”
mentioning
confidence: 99%
“…[34] derived formulas for the asymmetric exchange between two single magnetic ions embedded in a 1D-or 2DEG with Rashba SOC. A decade later, their result was generalized by allowing for finite uniform magnetization [35].…”
mentioning
confidence: 99%